Dynamic Timestamp-Based Authentication Techniques for Anti-Replay Attacks in LEO Satellite Networks - Hyun, Junyeol; Lee, Minwoo; Lim, Jaesung (Journal of Korean Institute of Communications and Information Sciences, 2022)
The wide accessibility of LEO satellites networks and exposed links are main factors that increase the threat of network attacks. An LEO satellite mega-constellation networks are more vulnerable to network attacks because they constitute extensive communication links in outer space. Especially the characteristics of dynamically varying propagation delay time between end-to-end constellation in LEO satellite networks increase the threat of replay attacks in authentication. This paper proposes a technique to use dynamic timestamps resistant to network replay attacks. To this end, this paper suggests the technique to calculate the allowable range of dynamic timestamps using the delay of inter-satellite links. And the authentication procedure was improved to use the dynamic timestamps. Through simulations, it was confirmed that the proposed technique could reduce the threat of regenerative attacks.
Keywords: Authentication; LEO Satellite Mega-Constellation; Propagation Delay; Replay Attack